1995
DOI: 10.1177/000331979504600805
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate-Corrected Ankle-to-Arm Index in the Diagnosis of Moderate Lower Extremity Arterial Disease

Abstract: In screening for LEAD in the general population with the use of AAI at rest, the authors suggest that the heart rate at which arterial pressure measurements are performed should be reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Interestingly, HR was correlated negatively with ABI in the Mongolian subjects, which is consistent with earlier findings. 17,18 In the Japanese subjects, the SBP was negatively correlated with ABI, which is also consistent with the earlier results. 19 Thus, although differences in the correlation pattern of CAVI and ABI with other atherosclerotic parameters between young Mongolian and Japanese subjects were identified, the reasons are unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, HR was correlated negatively with ABI in the Mongolian subjects, which is consistent with earlier findings. 17,18 In the Japanese subjects, the SBP was negatively correlated with ABI, which is also consistent with the earlier results. 19 Thus, although differences in the correlation pattern of CAVI and ABI with other atherosclerotic parameters between young Mongolian and Japanese subjects were identified, the reasons are unclear.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, some studies demonstrated that there was an inverse correlation between ABI and HR [15][16][17]. Abraham et al reported that in screening for PAOD in the general population with the use of ABI, the HR at which arterial pressure measurements were performed should be mentioned [16]. Our previous study also showed that ABI decreased significantly when HR was increased either by atrial or ventricular pacing in young and middle-aged patients without significant organic heart disease [17].…”
Section: Discussionmentioning
confidence: 82%
“…They suggested that decreased ABI following exercise was due to turbulence at high flow levels, rather than the shunting of blood to active muscles in exercise [24]. In addition, some studies demonstrated that there was an inverse correlation between ABI and HR [15][16][17]. Abraham et al reported that in screening for PAOD in the general population with the use of ABI, the HR at which arterial pressure measurements were performed should be mentioned [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this latter study, the predictive value of HR was significant even after adjustment for ABI. In one study [129], ABI was inversely correlated with HR in young healthy men, suggesting that the HR at which ABI is determined should be reported. However, there is no evidence whether the HR-corrected ABI would be a stronger risk predictor.…”
Section: Hr and Abimentioning
confidence: 99%